SIAIP position paper: provocation challenge to antibiotics and non-steroidal anti-inflammatory drugs in children - Carlo Caffarelli; Fabrizio Franceschini; Davide Caimmi; Francesca Mori; Lucia Diaferio; Dora Di Mauro; Carla Mastrorilli; Stefania Arasi; Simona Barni; Paolo Bottau; Silvia Caimmi; Fabio Cardinale; et al. (BMC, 2018)
Abstract Drug hypersensitivity reactions (DHRs) in childhood are mainly caused by betalactam or non-betalactam antibiotics, and non-steroidal anti-inflammatory drugs (NSAIDs). Laboratory tests for identifying children who are allergic to drugs have low diagnostic accuracy and predictive value. The gold standard to diagnose DHR is represented by the drug provocation test (DPT), that aims of ascertaining the causative role of an allergen and evaluating the tolerance to the suspected drug. Different protocols through the administration of divided increasing doses have been postulated according to the type of drug and the onset of the reaction (immediate or non immediate reactions). DPT protocols differ in doses and time interval between doses. In this position paper, the Italian Pediatric Society for Allergy and Immunology provides a practical guide for provocation test to antibiotics and NSAIDs in children and adolescents.